Unveiling the Nexus Between ICT and Inclusive Growth in West Java Province - Gayatri, Tayasi Ditoresmi; Kartiasih, Fitri (Ministry of National Development Planning Republic of Indonesia/Bappenas, 2024)
Inclusive economic development has become a concern for many countries, including Indonesia. National economic development inclusivity continues to improve. Nationally, economic development inclusivity continues to improve, but disparities still exist in some regions, such as Java Island. West Java Province becomes the province with a relatively low Inclusive Economic Development Index (IPEI). Although its inclusivity rate is above the national average, West Java Province still faces issues of high poverty levels and inequality. This can be caused by various factors, including technological advancement. This research aims to provide an overview and assess the influence of ICT usage and other factors on the achievement of inclusive economic development in West Java Province for the period 2017-2022. The research results using panel data and fixed effect FGLS modelling show that variables such as mobile phone users, computer users, physical capital stock, and the Human Development Index (HDI) have proven to have a positive and significant impact on achieving inclusive economic development.